Forelimb muscle plasticity following unilateral cervical spinal cord injury. Issue 3 (March 2016) - Gonzalez‐Rothi, Elisa J.; Armstrong, Gregory T.; Cerreta, Anthony J.; Fitzpatrick, Garrett M.; Reier, Paul J.; Lane, Michael A.; Judge, Andrew R.; Fuller, David D.
ABSTRACT: Introduction: Motor dysfunction and muscle atrophy are well documented in the lower extremity after spinal cord injury. However, the extent and time course of myoplastic changes in forelimb musculature is not clear. Methods: Forelimb muscle morphology and fiber type were evaluated after high cervical hemilesion injury in rats. Results: There was significant atrophy of the ipsilateral extensor carpi radialis longus (ECRL) muscle at 2 weeks postinjury, which was subsequently reversed at 8 weeks postinjury. The triceps muscle showed minimal evidence of atrophy after spinal injury. No significant changes in fiber type were observed. Conclusions: These findings indicate a robust capacity for spontaneous myoplasticity after C2 hemisection injury but highlight differential capacity for plasticity within the forelimb muscles. Muscle Nerve 53: 475–478, 2016